Absorption enhancement in hole Interface layer free perovskite solar cells using periodic photonic nanostructures. (July 2019) - Gupta, Nikhil Deep
Highlights: Presenting Perovskite cell having 2D periodic nanostructures patterned MAPbI3 active layer. The proposed structure enhances the performance of the HIL free perovskite cell design. Comparison with Lambertian limits, bare cell and reference planar cell values. Optimization and analysis has been done for the absorption, reflection and transmission. Angular performance and electric field intensity study has also been done for the design. Abstract: The study of Hole Interface Layer (HIL) free Perovskite Material (PM) solar cells have shown good potential in the recent years to simplify the PM solar cells design. However, the elimination of HIL suffers from device performance degradation. Herein, the article presents the optical design and optimization study of the 2D periodic photonic nanostructured HIL free PM material active layer based solar cells. Methyl Ammonium Lead Iodide (MAPbI3 ) is used as a PM material. PM layer is itself designed as a periodic nanostructure, also known as Photonic Crystal (PhC) structures. The article deals with the demonstration of the theoretical optical study and optimization of all the required parameters to design a PhC structure based proposed design having only 100 nm PM active layer thickness. The article also presents the Lambertian limit values for light trapping for MAPbI3 solar cells. The paper deals with the comparison of the proposed design performance with the Lambertian values, bare cell and reference planar HIL free structure of same active layer thickness. The study predicts that the optical performance of the proposed structure based on periodic nanostructures greatly surpasses that of reference structure. There is a comparative enhancement of around 44% in the proposed design as compared to planar reference structure. The absorption enhancement is basically accounted to the better trapping of incident photons, reduction in reflections, improved diffraction capability and index matching due to periodic nanostructures patterning of active layer in the proposed design. The parameters have been optimized and calculated using rigorous coupled wave analysis (RCWA).